A theoretical investigation of energy efficiency improvement by coal pre-drying in coal fired power plants. (15th August 2016) - Xu, Cheng; Xu, Gang; Zhao, Shifei; Dong, Wei; Zhou, Luyao; Yang, Yongping
Highlights: The principles of power plant efficiency increase by coal pre-drying were revealed. Formulation of impacts of coal pre-drying on units and plants' performance. Large energy amount of dried coal contribute the largest to the efficiency increase. Larger initial moisture content induces greater power plant efficiency increase. Abstract: A theoretical investigation of the principles of energy efficiency improvement in coal-fired power plants by removing a portion of the coal moisture content was performed. The relationship between the degree of pre-drying and coal's energy flow rate, boiler efficiency and power auxiliary rate were comprehensively formulized and graphically presented. The performance of the coal pre-drying power plants using coals with different initial moisture content was also discussed. The results showed that, coal's energy flow rate would increase by 0.6–1.5% as 0.1 kg moisture was removed per kg raw coal. The boiler efficiency would increase by 0.4–0.5% and the power auxiliary rate would slightly decrease by ∼0.2%. Eventually, the net efficiency of the power plant could increase in the range of 0.6–0.9%. Economic evaluation showed that the power plant performed more economically compared with the plant without coal pre-drying. This work provides a broadly applicable approach to formulaically revealing the principles of energy efficiency improvement in power plants by coal pre-drying.